Optimization of a protocol for cryopreservation of the spermatophore and sperm mass of the whteleg shrimp Litopenaeus vannamei (Boone, 1931) - Dominguez Mendoza, Luz Fernanda (2020)
The effect of six cryoprotective solutions based on MgCl2 and methanol, in addtion with sucrose and 10% Aloe vera gel or 10% egg yolk, on the sperm viability in spermatophore and sperm mass of Litopenaeus vannamei was evaluated. Besides, cooling rates of -0.5, -1 and -2 °C/min were used until temperature reached -35, -80 and -100 °C prior to immersion in liquid nitrogen. The sperm viability rate was determined by eosin-nigrosin staining. The results showed that the solutions based on MgCl2, sucrose plus egg yolk or Aloe vera gel better preserved sperm viability in spermatophore (82.8 ± 2.3% and 72.6 ± 3.1%) and in sperm mass (83.4 ± 2.5% and 76 ± 1.1%) without significant differences with the control group (p>0.05). The freezing curve showing less damage in spermatophore started from 25 °C and reached -35 °C with a rate of -1 °C/min using a cryoprotective solution with egg yolk and MgCl2, showing a sperm viability greater than 80% without significant differences with the control group (p>0.05), and a rate of -2 °C/min in the same temperature range for the group with sperm mass and a solution based on Aloe vera gel. In conclusion, the use of a solution based of MgCl2, sucrose, Aloe vera gel or egg yolk and at a cooling rate of -1 °C/min or -2 °C/min until reaching -35 °C allows a successful freezing of spermatophores or sperm of Litopenaeus vannamei.